Penerapan konseling kelompok dengan teknik behavioral contract dalam menurunkan perilaku indisipliner siswa Sekolah Menengah Pertama - Imaniyah, Wildahilyatul; Titi Pratitis, Niken (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Disciplinary problems among students, such as tardiness, truancy, and lack of readiness to learn, remain an issue at SMPN 17 Mataram. This study examines the impact of behavior contracts on reducing these behaviors among five eighth-grade students with high rates of disciplinary issues. A qualitative approach with a case study design was used. The subjects (AI, MS, AZ, RS, AA) were selected based on the guidance counselor's recommendations. Data were collected through interviews with the guidance counselor and students, non-participant observation at the school gate for three days, focus group discussions, and documentation of attendance records. The intervention consisted of six group counseling sessions, utilizing behavior contract techniques to establish behavioral goals, written contracts, journal monitoring, and positive reinforcement. Thematic data analysis was conducted through coding and triangulation of sources. The results showed that indiscipline was related to weak self-regulation, irregular sleep patterns, excessive use of gadgets, peer conformity, and minimal parental supervision. After the intervention, the frequency of tardiness decreased, truancy stopped, readiness to learn increased, and sleep patterns and personal responsibility improved. These findings prove that group counseling with behavior contracts is effective as a guidance strategy to reduce indiscipline and foster discipline in junior high schools.